Utilização de polímero hidroabsorvente no meloeiro (Cucumis melon L.) sob diferentes lâminas de irrigação - Ferreira Demartelaere, Andrea Celina; Dutra, Indalecio [UNESP]; Vieira Alves, Samara Sibelle; da Silva Teofilo, Taliane Maria; Alves, Simone Vieira (Univ Fed Rural Semi-arido-ufersa, 2009)
This work was carried out to evaluate the use of a hydrogel polymer in melon crop under different irrigation depths, with the objective of improve water retention, and efficiency of water and nutrient utilization by plants. One trial consisted of two treatments with four replications: a treatment with irrigation depth corresponding to 75% of gross depth and 27g of the soil conditioner per plant; the control with irrigation depth equal to the gross depth and without conditioner. The following characteristics were evaluated: root length, yield and quality of melon fruits. Root growth was bigger in the plants where soil conditioner was used. Use of soil conditioner provided an increase on melon yield and number of fruits per linear meter. Mean fruit weight and total soluble solids were not influenced by soil conditioner application and irrigation depth reduction.

Este trabalho foi desenvolvido para avaliar a utilização de um polímero hidroabsorvente na cultura do melão sob diferentes lâminas de irrigação, visando maior retenção de água e melhor aproveitamento da água e nutrientes pelas plantas. Foram utilizados dois tratamentos com quatro repetições: um tratamento com aplicação de 75% da lâmina bruta de irrigação e 27g de condicionador de solo; a testemunha, sem redução da lâmina de irrigação nem aplicação de condicionador. As características avaliadas foram: tamanho das raízes, produtividade e qualidade dos frutos. O crescimento do sistema radicular foi maior nas plantas onde se utilizou o condicionador de solo. Foi observada maior produtividade e número de frutos por metro linear em função da aplicação do condicionador de solo. O peso médio dos frutos e o teor de sólidos solúveis totais não foram influenciados pela aplicação do condicionador de solo e redução da lâmina de irrigação.
Use of hydrogel polymer in melon under different irrigation depths
Keywords: Cucumis melo L.; soil conditioner; water saving